Synopsis of the genus Neoeutrypanus Monné, 1977 (Coleoptera, Cerambycidae, Lamiinae), with the description of two new species - Botero, Juan Pablo; Monné, Miguel A. (Zootaxa, 2015)
Two new species of Neoeutrypanus Monné, 1977 are described: N. llanero sp. nov. from Colombia (Meta Department), and N. dentatus sp. nov. from Bolivia (La Paz Department). A key to species of Neoeutrypanus is provided and new distributional data for N. decorus (Bates, 1881) and N. mutilatus (Germar, 1824) are given.